2017
DOI: 10.1016/j.fertnstert.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Update on fertility preservation from the Barcelona International Society for Fertility Preservation–ESHRE–ASRM 2015 expert meeting: indications, results and future perspectives

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(114 citation statements)
references
References 77 publications
0
101
0
7
Order By: Relevance
“…However, in the vast majority of cancer patients, only 1 round of stimulation will be possible, and the number of oocytes retrieved has been found to be negatively correlated with age, but not with the type of cancer . Although oocyte/embryo vitrification is currently used routinely for young women requiring FP, the evidence regarding outcomes of IVF for cancer patients who have returned to use their stored oocytes, is scarce. The hitherto largest study, counting a cohort of 80 cancer patients, recently reported a cumulative live birth rate in young cancer patients (≤35 years) of only around 40%, whereas the percentage was markedly higher (around 70%) in the age‐matched group of elective freezers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the vast majority of cancer patients, only 1 round of stimulation will be possible, and the number of oocytes retrieved has been found to be negatively correlated with age, but not with the type of cancer . Although oocyte/embryo vitrification is currently used routinely for young women requiring FP, the evidence regarding outcomes of IVF for cancer patients who have returned to use their stored oocytes, is scarce. The hitherto largest study, counting a cohort of 80 cancer patients, recently reported a cumulative live birth rate in young cancer patients (≤35 years) of only around 40%, whereas the percentage was markedly higher (around 70%) in the age‐matched group of elective freezers .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the most prominent include cryopreservation of mature oocytes or embryos, if the woman has a partner. Due to the widespread knowledge on controlled ovarian stimulation (COS) and in vitro fertilization (IVF) these methods are currently regarded as the preferred options for postpubertal patients . The established technique of COS secures multiple follicles growing to the preovulatory stage, enabling aspiration of mature oocytes, which are subsequently vitrified before or after fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Women treated with cyclophosphamide should be informed of the subsequent infertility risk, as >80% of them wish to preserve their fertility . In adults, the first established option is oocyte/embryo cryopreservation . However, estradiol elevations induced by COS could aggravate SLE.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Similar figures can be found in our center (Figure ). These non‐oncological indications primarily include immunological, gynecological, hematological, or genetic pathologies . Ovarian failure can be induced either by the pathology itself (genetic disorders, autoimmune pathologies, inflammatory or intrinsic disorders), or by medical (eg immunosuppression using cyclophosphamide) or surgical treatments involving the ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is currently considered the most established technique in women who want to freeze eggs for medical reasons, such as cancer, autoimmune diseases, medical conditions causing ovarian insufficiency, and hematopoietic stem cell transplantation. Finally, it allows the reproductive autonomy of women and can be used for elective fertility preservation in women who are conscious of age‐related fertility decline but are not ready to become pregnant . In this regard, time to egg retrieval, age and number of oocytes available for freezing are decisive factors to optimize the cumulative chance of pregnancy with frozen oocytes .…”
Section: Introductionmentioning
confidence: 99%